HUBUNGAN ANTARA SELF ANXIETY DAN INTELLIGENCE QUOTIENT TERHADAP KEMAMPUAN PENALARAN MATEMATIS SISWA SMA: Abstrak, Pendahuluan, Metode, Hasil dan Pembahasan Kesimpulan, Referensi - Ayu Cahyani; Alifah Nabila Azzahra; Doi'fan Destara Putra; Rosida Rakhmawati Muhammad; Bambang Sri Anggoro (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
This study aims to explore the relationship between self anxiety, intelligence quotient (IQ), and mathematical reasoning ability in senior high school students. The approach used in this study was a quantitative method with a correlational design, which involved the application of partial regression and multiple regression analysis. The research sample consisted of 31 students selected from two schools in Bandar Lampung, namely SMA Negeri 5 and SMA Negeri 15, which were taken from a population of 56 grade XI students. Data in this study were collected through test and non-test instruments. The analysis showed that self anxiety and Intelligence Quotient contributed 55.9% to students' mathematical reasoning ability, while the remaining 44.1% was influenced by other variables that were not the focus of this study.